2008
DOI: 10.1371/journal.pone.0003923
|View full text |Cite
|
Sign up to set email alerts
|

Media Ion Composition Controls Regulatory and Virulence Response of Salmonella in Spaceflight

Abstract: The spaceflight environment is relevant to conditions encountered by pathogens during the course of infection and induces novel changes in microbial pathogenesis not observed using conventional methods. It is unclear how microbial cells sense spaceflight-associated changes to their growth environment and orchestrate corresponding changes in molecular and physiological phenotypes relevant to the infection process. Here we report that spaceflight-induced increases in Salmonella virulence are regulated by media i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
170
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 137 publications
(180 citation statements)
references
References 30 publications
8
170
2
Order By: Relevance
“…Several studies already reported a more apparent bacterial response when cultivation in space flight, and space flight analogs was performed on rich medium Leff, 2004, 2006;Benoit and Klaus, 2007;Wilson et al, 2008). However, the difference in growth medium composition is probably not the only factor responsible for the difference in expression pattern for MESSAGE 2 and BASE-A.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies already reported a more apparent bacterial response when cultivation in space flight, and space flight analogs was performed on rich medium Leff, 2004, 2006;Benoit and Klaus, 2007;Wilson et al, 2008). However, the difference in growth medium composition is probably not the only factor responsible for the difference in expression pattern for MESSAGE 2 and BASE-A.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, numerous in-flight studies have confirmed that space flight can have a pronounced effect on a variety of microbial parameters including changes in microbial proliferation rate, cell morphology, cell physiology, cell metabolism, genetic transfer among cells and viral reactivation within the cells (reviewed in Leys et al, 2004;Nickerson et al, 2004;Nicholson et al, 2005;Klaus and Howard, 2006). However, previous studies have also shown that the results from space flight and space flight analog experiments can radically differ when using different bacteria or when using the same bacterium but different culture media Leff, 2004, 2006;Benoit and Klaus, 2007;Wilson et al, 2008;Leys et al, in press).…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradation of critical materials can result in system failures that may endanger crews. Evidence gained during the SSP suggests that infectious diseases and allergic responses may increase on long exploration missions due to sustained immune deficiencies (11)(12)(13)(14)(15) and increased virulence of some microorganism (7)(8)(9)(10). …”
Section: Identification Of Microbiological Hazards and Risksmentioning
confidence: 99%
“…Our understanding of the effects of spaceflight on these life forms was greatly enhanced during the Space Shuttle Program (SSP). Some bacteria and fungi were shown to be more virulent as a result of spaceflight (7)(8)(9)(10). Immune studies showed decreases in innate immunity, cell mediated immunity (11)(12)(13)(14)(15), and increased latent virus reactivation (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, microarray analysis revealed that S. Typhimurium iprA was upregulated in cultures inoculated and grown during spaceflight (compared to identically grown ground controls) and in cultures grown under low-fluid-shear RWV conditions (compared to RWV controls in which low-fluid-shear conditions were disrupted) (6,7). Interestingly, both spaceflight and RWV growth conditions increase the virulence of S. Typhimurium assayed using murine infection models (6,9,10). However, to our knowledge, the iprA gene is uncharacterized in the literature beyond these observations.…”
mentioning
confidence: 99%